2018
DOI: 10.1098/rspb.2018.1577
|View full text |Cite
|
Sign up to set email alerts
|

Experimental disturbances reveal group-level costs of social instability

Abstract: In group-living species, social stability is an important trait associated with the evolution of complex behaviours such as cooperation. While the drivers of stability in small groups are relatively well studied, little is known about the potential impacts of unstable states on animal societies. Temporary changes in group composition, such as a social group splitting and recombining (i.e. a disturbance event), can result in individuals having to re-establish their social relationships, thus taking time away fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 45 publications
1
59
0
Order By: Relevance
“…Advances in our ability to study and analyse social behaviour [9], especially in the wild, have highlighted the widespread effects of social behaviour on fitness. There is now clear evidence that individuals can exhibit consistent differences in their social network position [10][11][12][13], which are resilient to environmental change [14,15] (but see [16]), and that these differences can translate to consequences for fitness [17][18][19][20][21]. For example, being more central in a network has been linked to having access to more information [22], but also being more exposed to disease [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in our ability to study and analyse social behaviour [9], especially in the wild, have highlighted the widespread effects of social behaviour on fitness. There is now clear evidence that individuals can exhibit consistent differences in their social network position [10][11][12][13], which are resilient to environmental change [14,15] (but see [16]), and that these differences can translate to consequences for fitness [17][18][19][20][21]. For example, being more central in a network has been linked to having access to more information [22], but also being more exposed to disease [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that in other social animals, sparse and specialized social networks can be associated with fitness benefits (Stroeymeyt et al 2018); hence, a breakdown to this organization may incur costs (Maldonado-Chaparro et al 2018). Testing our proposed mechanism for the link between hormone-mediated behavior and network dynamics will require direct observation of the individual social behaviors that occur within dyads, and how these behaviors change through time.…”
Section: Discussionmentioning
confidence: 95%
“…We also observed that larger leks Introduction Behavioral interactions are the foundation of social network structures that can vary through time, among populations, and across species. Network structures play an important role in many ecological and evolutionary processes, including the spread of diseases (Sah et al 2018;Stroeymeyt et al 2018), the transmission of information and resources (Aplin et al 2012;Maldonado-Chaparro et al 2018), and selection on individual behavior (Ohtsuki et al 2006). A major challenge is understanding how individual-level factors, such as physiological and behavioral mechanisms, scale up to drive the emergent structural properties of social groups (Krause & Ruxton 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, there were no such survival impacts for nontranslocated hihi. Gaining associates in an unknown environment may be beneficial by facilitating crucial behaviours that impact on survival, such as efficient co-feeding (Maldonado-Chaparro et al, 2018); alternatively, individuals that survive longest may also have more opportunity to gain associates. Whether this beneficial relationship becomes clearer with more power (i.e.…”
Section: Discussionmentioning
confidence: 99%